Investigating Pre-Competition-Related Discrete Emotions and Unaccustomed Religious Coping among Elite Student-Athletes: Implications for Reflexive Practice - Hagan, John Elvis (Religions (Basel, Switzerland ), 2021)
Given that elite athletes experience a wide range of different emotions (e.g., anxiety, anger, dejection, excitement) toward upcoming sporting environments, it is surprising that researchers have given limited attention to the linkages between varied emotional experiences and diverse coping (unaccustomed) among athletes from diverse backgrounds. This study investigated the impact of religious coping, as opposed to conventional psychological skills, to ascertain whether these coping options influence elite student-athletes’ emotional reactions across gender, competitive status, and religion. Using a descriptive cross-sectional survey design, self-reported discrete emotions and religious coping were measured with the Sport Emotion Questionnaire (SEQ) and Brief-Religious Coping Scale (Brief RCOPE) after 300 selected athletes were conveniently chosen. A factorial multivariate analysis of covariance (MANCOVA) after controlling for age revealed no significant interactions for between-subject factors (gender, status, religion) across all the discrete emotions and religious coping dimensions. However, significant main effects were realized for competitive status and religion on only anger, anxiety, dejection, and negative religious coping. A follow-up multiple regression analysis identified religion as the most significant predictor of anger, anxiety, and dejection, whereas competitive status was the most associated variable for negative religious coping. Current findings suggest that athletes’ unpleasant or negative emotions were linked to negative religious coping, a maladaptive coping mechanism that may hinder attaining optimal emotional state prior to competition. Therefore, these athletes need purposeful strategies (e.g., positive religious coping, motivational strategies) that may improve weakened beliefs based on their struggles before competition. The development of appropriate psychological intervention framework that maintains respect for athletes’ religious identities for improved psychological well-being is also warranted.